(8x-12)=(5x+3)

Simple and best practice solution for (8x-12)=(5x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x-12)=(5x+3) equation:



(8x-12)=(5x+3)
We move all terms to the left:
(8x-12)-((5x+3))=0
We get rid of parentheses
8x-((5x+3))-12=0
We calculate terms in parentheses: -((5x+3)), so:
(5x+3)
We get rid of parentheses
5x+3
Back to the equation:
-(5x+3)
We get rid of parentheses
8x-5x-3-12=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5

See similar equations:

| 2x+11=x+10 | | 37=3w+10 | | -4(7x+8)=28x-32 | | u/2+9=14 | | 5u=u=16 | | 2x(x+5)=102 | | (10x61)+(x+10)=180 | | 8.8x-2.4=41.6 | | 8.8x-24=41.6 | | 2n=n+26 | | 15=−45+5n | | .1v+3.4=-7.2 | | 5x^2-30x-400=0 | | 10-3(z-2=5z+7 | | 4y+6y=3y-218 | | 61y=20(3y+21) | | 5x^2-30x+400=0 | | 10x+10=3-4x | | 3n+8=5n-15 | | 12m+3m=18 | | 13x-4=10x+2 | | -8x-7(6x+6)=6-2x | | 5x^2-42x+400=0 | | u+3.56=6.39 | | -x–9=-13 | | 17x+18=50 | | 4(3-5w)=-11 | | (y/6)-1=6 | | 9x+6=2x-36 | | 6.8x-3.6=37.2 | | -16/9=-4/3(5/3n | | 9x-6=2x-36 |

Equations solver categories